THE ROLE OF INVESTIGATORS CIVIL SERVANTS OF NORTH SUMATERA PROVINCE IN THE FRAMEWORK OF ACTIVITIES OF ILLEGAL LOGGING CRIMINAL ACTIONS - Lavita Raradanti; Mahzaniar Mahzaniar; Halimatul Maryani; Adawiyah Nasution (Universitas Labuhanbatu, 2023)
Illegal logging activities or illegal/illegal logging activities are illegal logging activities by violating laws and regulations that have been going on for a long time in Indonesia, especially in North Sumatra Province. The purpose of this research is to find out the process of investigating civil servant investigators (PPNS) in the context of taking action against perpetrators of illegal logging in North Sumatra and to find out what obstacles are faced by investigators of civil servants (PPNS) in the context of investigating perpetrators of criminal acts. illegal logging crime. This research was carried out by direct researchers in the field with literature studies, namely by conducting searches of books, and literature and also conducting direct interviews with related parties, Civil Servant Investigators (PPNS). Based on the research conducted by the authors, it can be concluded that the obstacles faced by Civil Servant Investigators (PPNS) in handling forestry crimes, in general, are weak coordination between law enforcers. The main actors (intellectualactors) which are difficult to penetrate by law, the existence of regional autonomy, lack of facilities and infrastructure, and limited funds. Countermeasures against Illegal logging can run well and as expected, it is necessary to increase the eradication of Illegal logging crimes, prepare law enforcement officials both in terms of quality and quantity, and enforce regulations and provisions on forestry as well as possible to minimize provisions as small as possible the crime of illegal logging throughout Indonesia, especially in North Sumatra Province.Keywords: Civil Servant Investigator; Enforcemen; Illegal Logging